Corruption Perception in the Czech Republic - Naxera Vladimír (Politics in Central Europe, 2015)
This paper is focused on the issue of corruption perception in the Czech Republic. After introducing the general framework for corruption perception in post-communist countries, this paper uses the Czech Republic as an example of the ways in which corruption is perceived, the areas Czech citizens feel are most plagued by corruption, and the ways in which corruption perception has transformed in terms of post-communist developments. This paper points out the differences in corruption perception among Czech citizens, the media and political parties and their representatives. The conclusion of the paper attempts to answer the question of how corruption perception has affected the overall perception of the democratic regime in the Czech Republic. It also asks questions regarding how this has influenced the evaluation of democracy and the relationship between Czech citizens and political institutions, including individual political parties.